2019
DOI: 10.3390/brainsci9070151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Mental Stimulation Program of Computer and Internet Learning on Cognitive Functions and Wellbeing in Older Community-Dwelling Mexicans

Abstract: Background: It has been reported that Mental Stimulation (MS) has a positive effect on cognitive functions and wellbeing. In this sense, different training activities have been proposed for MS such as theater, learning a new language, playing a musical instrument and computing, however, there are few studies on older adults in Latin American countries. For this reason, the purpose of the present study was to determine the effect of a mental stimulation program (MSP) of computer and Internet learning on cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Subjects across eight studies revealed an increase in feelings of community, sociability, and pleasure following formal learning (Ellis, 2018; Kinney & Rentz, 2005; Mendoza-Ruvalcaba & Arias-Merino, 2015; Panayotoff, 1993; Richeson et al, 2007; Rusted et al, 2006; Sánchez-Nieto et al, 2019; Ullán et al, 2013). There was also a reduction in loneliness reported for three computer and internet training interventions (Blažun et al, 2012; Chilcott & Smith, 2011; White et al, 2002), while depression was reported to be reduced in four studies across various learning types (Rusted et al, 2006; Sánchez-Nieto et al, 2019; Shapira et al, 2007; White et al, 2002). Two studies reported that previous formal education, and higher education levels increased intervention success/adoption (Cutler et al, 2016; Richeson et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects across eight studies revealed an increase in feelings of community, sociability, and pleasure following formal learning (Ellis, 2018; Kinney & Rentz, 2005; Mendoza-Ruvalcaba & Arias-Merino, 2015; Panayotoff, 1993; Richeson et al, 2007; Rusted et al, 2006; Sánchez-Nieto et al, 2019; Ullán et al, 2013). There was also a reduction in loneliness reported for three computer and internet training interventions (Blažun et al, 2012; Chilcott & Smith, 2011; White et al, 2002), while depression was reported to be reduced in four studies across various learning types (Rusted et al, 2006; Sánchez-Nieto et al, 2019; Shapira et al, 2007; White et al, 2002). Two studies reported that previous formal education, and higher education levels increased intervention success/adoption (Cutler et al, 2016; Richeson et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there was an increased sense of self and life satisfaction and an increase in self-confidence or confidence with computer use. Subjects across eight studies revealed an increase in feelings of community, sociability, and pleasure following formal learning (Ellis, 2018;Kinney & Rentz, 2005;Mendoza-Ruvalcaba & Arias-Merino, 2015;Panayotoff, 1993;Richeson et al, 2007;Rusted et al, 2006;Sánchez-Nieto et al, 2019;Ullán et al, 2013). There was also a reduction in loneliness reported for three computer and internet training interventions (Blažun et al, 2012;Chilcott & Smith, 2011;White et al, 2002), while depression was reported to be reduced in four studies across various learning types (Rusted et al, 2006;Sánchez-Nieto et al, 2019;Shapira et al, 2007;White et al, 2002).…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Publicación bimestral se han limitado a brindan orientaciones y consultas médicas a través de los programas de "Teleasistencia" y "Telecuidado". 25 Por lo anterior, la "Telegerontología Comunitaria", representa una estrategia factible que se debe promover y desarrollar para problemas emergentes como la Covid-19. Aunque también constituye una opción que permitirá fortalecer los vínculos entre las personas mayores con la población joven, además de que el uso de la tecnología per se es una opción para la estimulación mental.…”
Section: Boletín De La Evidenciaunclassified